2021
DOI: 10.5755/j02.ms.27679
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Properties of Electropolished AISI 316L Austenitic Biomaterial in Relation to Electropolishing Conditions

Abstract: Electropolishing is recommended for various biomedical applications of austenitic biomaterials because it enables to achieve high brightness, very low surface roughness, excellent corrosion resistance and reduced bacterial attachment without residual surface tensions. The quality of an electropolished surface depends strongly on the composition of used electrolyte and on the applied electropolishing conditions. In this article the corrosion properties of eight AISI 316L surfaces electropolished in the same sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
(31 reference statements)
0
2
2
Order By: Relevance
“…It points to the high corrosion resistance and biomedical safety with the minimum metal release into the human body environment [16,46,47] that correlates with the results of the performed independent electrochemical corrosion tests. Unlike these results, in the exposure test performed under the same conditions on the EP surface of 316L stainless steel, the authors [28] observed more pronounced pitting corrosion damage and higher corrosion rates (dependent on EP conditions 0.013-0.024 g/(m 2 .day)). The received surface (Figure 8a) showed the lower quality of the passive film, which enabled the local penetration of the chloride anions in numerous places and the initiation The received surface (Figure 8a) showed the lower quality of the passive film, which enabled the local penetration of the chloride anions in numerous places and the initiation of pitting corrosion.…”
Section: Exposure Immersion Testcontrasting
confidence: 56%
See 3 more Smart Citations
“…It points to the high corrosion resistance and biomedical safety with the minimum metal release into the human body environment [16,46,47] that correlates with the results of the performed independent electrochemical corrosion tests. Unlike these results, in the exposure test performed under the same conditions on the EP surface of 316L stainless steel, the authors [28] observed more pronounced pitting corrosion damage and higher corrosion rates (dependent on EP conditions 0.013-0.024 g/(m 2 .day)). The received surface (Figure 8a) showed the lower quality of the passive film, which enabled the local penetration of the chloride anions in numerous places and the initiation The received surface (Figure 8a) showed the lower quality of the passive film, which enabled the local penetration of the chloride anions in numerous places and the initiation of pitting corrosion.…”
Section: Exposure Immersion Testcontrasting
confidence: 56%
“…It points to the high corrosion resistance and biomedical safety with the minimum metal release into the human body environment [16,46,47] that correlates with the results of the performed independent electrochemical corrosion tests. Unlike these results, in the exposure test performed under the same conditions on the EP surface of 316L stainless steel, the authors [28] observed more pronounced pitting corrosion damage and higher corrosion rates (dependent on EP conditions 0.013-0.024 g/(m 2 •day)).…”
Section: Exposure Immersion Testcontrasting
confidence: 55%
See 2 more Smart Citations
“…While 14 minutes electropolishing time was found to give the maximum gloss, this study also proved that increasing the time higher would worsen the surface [17] . Electropolishing temperature that resulted in lower roughness parameters and minimized the possibility of bacterial attachment was identified [18] .…”
Section: Introductionmentioning
confidence: 99%